Placenta accreta spectrum: Is placental invasion real? Placenta accreta spectrum - Esercan , Alev; Ekmekci , Emre; Coskun , Ferhat (Journal of Surgery and Medicine, 2023)
Background/Aim: The description of placenta accreta spectrum disorder (PAS) has undergone significant changes. However, its association with obstetric morbidity and mortality has become even more important. Therefore, we aimed to assess the histopathologic evaluation of PAS patients who underwent a hysterectomy. Methods: We conducted a retrospective study of all pathology reports from patients with peripartum hysterectomies at Sanliurfa Training and Research Hospital diagnosed with PAS. The study included 45 patients with a cesarean hysterectomy due to a preoperative placenta accreta spectrum disorder diagnosis. Hysterectomy specimens were evaluated based on placental invasion and myometrial defect at the site of the placenta. Results: Out of 45 patients diagnosed with placenta accreta spectrum disorder who underwent a hysterectomy, only 17 (37.8%) had a histological diagnosis supporting the placental invasion. The histological diagnosis was consistent in 20 (44.4%) patients, indicating that the placenta protruded from a uterine wall defect without placental invasion. In eighth (17.8%) patients, the histopathological diagnosis was consistent with a histologically normal placenta. Conclusion: The primary pathology of the disorder is variable, and the main issue is the association of the placenta with defective myometrium. Although a more alarming definition, such as invasion, should be avoided, PAS should not be underestimated due to its high mortality.